Կիսկիմի գավառի հայ բնակչությունը XIX դարի 30-70-ական թթ․ - Ակոպով, Արկադի («Նաիրի» հրատ.)
В 1831 г. в Османской империи произошли административные перемены, в результате которых одна из провинций исторической Армении – Тайк, полностью вошла в состав Эрзурумского эялета. Среди тайкских регионов самой армянозаселенною стала Кискимская каза (область), которая располагалась в бассейне реки Чорох. Известными армянскими селениями Кискимской казы являлись Верхний и Нижний Мохуркуты, Кармирк, Цеткунц, Кудрашен, а так же Хоторджурская община. В середине XIX в. состояние армян Кискимской казы ухудшалось. Согласно К. Коху, только два армяно-католических селения – Кармирк и Хоторджур, были полностью заселены армянами, а в остальных селениях армяне проживали рядом с мусульманами. Согласно историческим источникам и архивным материалам, во второй половине XIX века в Кискимской казе проживало более 1100 дворов армян с населением 9800 человек. In 1831, the Ottoman Empire implemented administrative changes, as a result of which, Tayk, one of the provinces of historical Armenia, became a part of the Erzurum Eyalet. Among the regions of Tayk, the Kaza (district) of Kiskim, located in the basin of the Chorokh River, had the largest Armenian population. The most famous Armenian villages of the Kiskim district were Upper and Lower Mohurkuts, Karmirk, Tsetkunts, Tandzut, Kudrashen, as well as the Khotorjour community. In the mid-19th century, the living conditions of the Armenians of Kiskim worsened. According to K. Koch, only two Armenian-Catholic villages, Karmirk and Khotorjour, were completely inhabited by Armenians, while in the rest of the villages Armenians lived alongside Muslims. According to historical sources and archival documents, in the second half of the 19th century, there were more than 1100 Armenian households made up of some 9800 Armenians in the district of Kiskim.
Keywords: Աղբյուրագիտություն; Պատմագրություն; Վիճակագրություն